Education in the Family According to Ki Hadjar Dewantara - Harahap, Wilda Deliana; Nirwana, Herman; Sukma, Dina (Yana Research, 2024)
This research aims to explore the importance of the family environment as the foundation for early childhood education before they are introduced to school and society. The method used is a literature study, with data collected from various sources such as books, journals, and previous research. The study emphasizes that the family is the most influential and perfect educational institution in shaping a child's character, morality, and personality. Family education must go hand in hand with formal education to produce a future generation that is intelligent, moral, and prepared to face complex social life. Therefore, it is crucial for parents to set a good example and act as role models in all aspects of life.